Therapeutic Cancer Vaccination With a Peptide Derived From the Calreticulin Exon 9 Mutations Induces Strong Cellular Immune Responses in Patients With CALR-Mutant Chronic Myeloproliferative Neoplasms - Handlos Grauslund, Jacob; Holmström, Morten Orebo; Jørgensen, Nicolai Grønne; Klausen, Uffe; Weis-Banke, Stine Emilie; El Fassi, Daniel; Schöllkopf, Claudia; Clausen, Mette Borg; Gjerdrum, Lise Mette Rahbek; Breinholt, Marie Fredslund; Kjeldsen, Julie Westerlin; Hansen, Morten; et al. (Frontiers in Oncology, 2021)
Background: The calreticulin (CALR) exon 9 mutations that are identified in 20 % of patients with Philadelphia chromosome negative chronic myeloproliferative neoplasms (MPN) generate immunogenic antigens. Thus, therapeutic cancer vaccination against mutant CALR could be a new treatment modality in CALR-mutant MPN. Methods: The safety and efficacy of vaccination with the peptide CALRLong36 derived from the CALR exon 9 mutations was tested in a phase I clinical vaccination trial with montanide as adjuvant. Ten patients with CALRmut MPN were included in the trial and received 15 vaccines over the course of one year. The primary end point was evaluation of safety and toxicity of the vaccine. Secondary endpoint was assessment of the immune response to the vaccination epitope (www.clinicaltrials.gov identifier NCT03566446). Results: Patients had a median age of 59.5 years and a median disease duration of 6.5 years. All patients received the intended 15 vaccines, and the vaccines were deemed safe and tolerable as only two grade three AE were detected, and none of these were considered to be related to the vaccine. A decline in platelet counts relative to the platelets counts at baseline was detected during the first 100 days, however this did not translate into neither a clinical nor a molecular response in any of the patients. Immunomonitoring revealed that 4 of 10 patients had an in vitro interferon (IFN)- ELISPOT response to the CALRLong36 peptide at baseline, and four additional patients displayed a response in ELISPOT upon receiving three or more vaccines. The amplitude of the immune response increased during the entire vaccination schedule for patients with essential thrombocythemia. In contrast, the immune response in patients with primary myelofibrosis did not increase after three vaccines. Conclusion: Therapeutic cancer vaccination with peptide vaccines derived from mutant CALR with montanide as an adjuvant, is safe and tolerable. The vaccines did not induce any clinical responses. However, the majority of patients displayed a marked T-cell response to the vaccine upon completion of the trial. This suggests that vaccines directed against mutant CALR may be used with other cancer therapeutic modalities to enhance the anti-tumor immune response.